Thalassaemia in Azerbaijan. Issue 3 (March 1994) - Kuliev, A M; Rasulov, I M; Dadasheva, T; Schwarz, E I; Rosatelli, C; Saba, L; Meloni, A; Gemidjioglu, E; Petrou, M; Modell, B
Abstract : beta thalassaemia is present throughout the southern regions of the former USSR. We have defined the clinical picture of the disorder, the spectrum of beta thalassaemia mutations, and the role of customary consanguineous marriage in Azerbaijan, where thalassaemia presents a public health problem of the same order as that in Greece. Contrary to earlier suggestions, we found that the common form of the disorder is typically severe. Typical Turkish, Mediterranean, Azeri, Kurdish, and Asian Indian mutations were found, consistent with the history of the region. The common Mediterranean beta 0 thalassaemia mutation (codon 39) was not found. Three mutations (codon 8-AA, IVS2-1 and IVS1-110) account for over 80% of beta thalassaemia genes. Consanguineous marriage appears to contribute relatively little to the frequency of affected births. These observations provide the basis for a thalassaemia prevention programme in Azerbaijan.